PERANCANGAN MEDIA PEMBELAJARAN GAME EDUKASI ADVENTURE BERBASIS MOBILE MATA PELAJARAN ILMU PENGETAHUAN ALAM PADA MATERI SISTEM PENCERNAAN MANUSIA KELAS VIII DI SMP N 18 SURAKARTA 2026 - Husain Nur Arifin; Suryanti, Hera Heru Sri; Widhoyoko, Yudhistiro Pandu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the difficulty students face in visualizing the abstract material of the human digestive system within the Merdeka Curriculum at SMPN 18 Surakarta, as well as the limited interactive media in the classroom. This study aims to design, develop, and test the feasibility of a 2D Android-based adventure educational game using GDevelop 5 as an interactive science learning medium. The development method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). System functionality was tested using Black Box Testing to ensure all program navigation runs normally before implementation. The results showed that the educational game